University Teacher Training Programs in Chile: Characteristics, Purposes, and Teaching Reflection - Perez-Lorca, A (UNIV CATOLICA SILVA HENRIQUEZ, 2022)
Training university faculty is considered a fundamental need for improving student learning. How academic development pro-grams train such faculty in psychoeducational knowledge is little known. However, one of the aspects included in the training is a reflection on practice since it plays a central role in how teachers organize their teaching and articulate theory. This paper aims to study teacher training programs in the Chilean university context and to analyze their pedagogical design concerning the teaching of reflection. Our work uses a mixed qualitative and quantitative method. We collected data through a questionnaire and ana-lyzed training proposals. We examined twenty programs from different Chilean Higher Education Institutions. Results point to the existence of training organization and implementation that differ in purpose and characterization if the teaching of reflec-tion is both a learning object and an innovative teaching practice in Higher Education.